Halogen⋯Halogen Interactions: Nature, Directionality and Applications. Issue 8 (13th March 2023) - Saha, Binoy K.; Veluthaparambath, Ragima V. P.; Krishna G., Vibha
Abstract: Halogen⋯halogen interaction is a highly debated and important topic in crystal engineering and supramolecular chemistry. There are controversies about the nature and geometry of these interactions. F, Cl, Br and I are the four halogens involved in these interactions. Very often the lighter and the heavier halogens behave differently. The nature of the interactions also depends upon the nature of the atom which is covalently bonded to the halogens. In this review different homo‐halogen⋯halogen, hetero‐halogen⋯halogen, halogen⋯halide interactions, their natures, and preferred geometries have been discussed. Different motifs of halogen⋯halogen interactions, interchangeability of the halogen⋯halogen interactions with other supramolecular synthons and interchangeability between different halogens and other functional groups also have been discussed. Some of the important applications, in which halogen⋯halogen interactions have been successfully employed, are mentioned. Abstract : Halogen⋅⋅⋅halogen interaction is a highly debated topic in supramolecular chemistry. How the concept of this interaction has been developed until date has been discussed from a historical perspective. Its nature, geometry and different groups of thoughts have been discussed. In the end, how these interactions have been successfully employed in different applications is also mentioned.